Onion (Allium cepa L.) Skin Waste Valorization: Unveiling the Phenolic Profile and Biological Potential for the Creation of Bioactive Agents through Subcritical Water Extraction - Esther Trigueros; Óscar Benito-Román; Andreia P. Oliveira; Romeu A. Videira; Paula B. Andrade; María Teresa Sanz; Sagrario Beltrán (MDPI AG, 2024)
Onion skin waste (OSW), the primary non-edible byproduct from onion processing, offers a renewable source of bioactive compounds. This study aims to valorize OSW through subcritical water extraction (SWE), aligning with a circular economy and biorefinery principles. SWE was carried out at 145 °C and 50 bar for 50 min in a discontinuous reactor, producing a phenolic-rich extract (32.3 ± 2.6 mg/g) dominated by protocatechuic acid (20.3 ± 2.5 mg/g), quercetin-4'-O-glucoside (7.5 ± 0.2 mg/g), and quercetin (3.2 ± 0.6 mg/g). Additionally, the extract contains sugars (207.1 ± 20.3 mg sucrose-Eq/g), proteins (22.8 ± 1.6 mg BSA-Eq/g), and free amino acids (20.4 ± 1.2 mg arginine-Eq/g). Its phenolic richness determines its scavenging activity against ●NO and O2●− radicals and its α-glucosidase and aldose-reductase inhibition without affecting α-amylase. Notably, the extract demonstrates significant α-glucosidase inhibition (IC50 = 75.6 ± 43.5 µg/mL), surpassing acarbose (IC50 = 129.5 ± 1.0 µg/mL) in both pure enzyme and cell culture tests without showing cytotoxicity to AGS, HepG2, and Caco-2 human cell lines. The extract's bioactivity and nutritional content make it suitable for developing antioxidant and antidiabetic nutraceutical/food components, highlighting SWE's potential for OSW valorization without using organic solvents.